Extracurricular Management Information System - Dimas Nurdiansyah; Fadhlan Hadyan Nadhir; Hasyifa Nur Fadhillah; Marjito Marjito; Asep Ririh Riswaya (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The extracurricular management information system aids educational institutions in efficiently managing extracurricular activities. These activities are vital for student development outside of the classroom. However, manual administration of extracurricular activities is time-consuming and challenging. In the digital age, extracurricular management information systems are necessary to enhance efficiency and effectiveness in managing these activities. This study aims to create and involve an extracurricular management information system that will enhance the efficiency and effectiveness of managing extracurricular activities in schools and educational institutions. This extracurricular management information system's construction employed a research technique encompassing needs analysis, system design, software development, implementation, and evaluation. During the needs analysis step, we conducted interviews with schools and educational institutions that have experience managing extracurricular activities. The interview results were used to design the system according to the user's needs. The findings of this analysis serve as a basis for developing suitable information systems. This research has developed software that utilizes cutting-edge technology to enable system access through various devices, such as PCs, cell phones, and tablets. In addition, we prioritize data security and user privacy during the development of this system. Implementing an extracurricular management information system has undergone testing in multiple schools and educational institutions. Evidence from the test results demonstrates that this method can enhance the effectiveness of overseeing extracurricular activities. The incorporation of cutting-edge technology enables users to access the system through various devices, including PCs, cellphones, and tablets, thereby enhancing user flexibility and accessibility. This system's implementation and testing have been limited to a small number of schools and educational institutions. An enormous scope is required to ensure the generalizability of the research outcomes.